Aktualisasi nilai-nilai ekologis ajran Tasawwuf dalam pelestarian lingkungan: Studi pada Tarekat Rowobayan - Ilham Tohari; Umar Faruq (Pustaka Peradaban, 2022)
The tarekat's involvement in environmental conservation efforts has not been explored much. It is because tarekat is generally only associated with efforts to strengthen spirituality. Sufism and Tarekat are often not involved in discussions on social and ecological issues. This article aims to examine the Rowobayan congregation related to environmental ethics and environmental conservation efforts. Rowobayan is a tarekat whose validity is recognized by the majority of Muslims and has a substantial role in the development of the tarekat in Indonesia. Thus, his teachings on environmental ethics can be ensured by Islamic law. So, the assumption that environmental ethics in it is influenced by the syncretistic mysticism movement that is widely developing in Indonesia. The study found that the values of environmental preservation in the teachings of Sufism in the Tarekat Rowobayan are based on the concept of the unity of existence, the caliphate and servitude, the values of universal compassion (rahmatan lil'alamin), and the zuhud. The actualization of these values in environmental conservation is by being wise and respecting nature, being active in taking roles and responsibilities to preserve nature, loving and having good character in interacting with nature, and simplicity in the consumption and management of natural resources.